Developing the library of Bagong Ilog Elementary School in Pasig City - Silvestre, Camille Jol P. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Developing the library of Bagong Ilog Elementary School was created to respond to the needs of its learners. The library has limited resources and the most of its books are outdated. Also, the library does not have a licensed librarian to manage the site which results to its unorganized collection of resources.